Understanding How Health Providers Identify Women with Postpartum Hemorrhage: A Qualitative Study - Bento, Silvana Ferreira; Borovac-Pinheiro, Anderson; Tanaka, Erika Zambrano; Silveira, Carla; Pacagnella, Rodolfo Carvalho (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Objective To identify how health providers recognize postpartum hemorrhage early and the difficulties involved in it.Methods An exploratory, descriptive study using a qualitative approach through a semi-structured interview technique. In total, 27 health professionals (nursing technicians, nurses, medical residents in Gynecology and Obstetrics, hired medical doctors, and medicine professors) working in a tertiary-level hospital of reference in women's health care in the State of São Paulo, Brazil, participated in the study through an invitation. After they accepted the invitation, they signed the free and informed consent form. All interviews were recorded and transcribed, and a thematic analysis was conducted. We found three analysis categories: a) perception of the severity: “there is something wrong with the women”; b) difficulties in the early diagnosis of postpartum hemorrhage; and c) the process to improve obstetrical care.Results Caregivers believe teamwork and communication should be improved. Besides the visual estimation of blood loss, the nursing team is attentive to behavioral symptoms like irritability, while the medical staff follow protocols and look for objective signs, such as altered vital signs.Conclusion Besides the objective evaluations, the subjective perceptions of the providers are involved in the clinical judgement regarding the diagnosis of postpartum hemorrhage, and this should be included in a broader diagnosis strategy.
Keywords: postpartum hemorrhage; diagnosis; clinical judgment; qualitative research; health professionals